Evaluasi Lahan Sebagai Dasar Pengembangan Tanaman Buah-Buahan Unggulan Di Kecamatan Tinangkung Selatan Kabupaten Banggai Kepulauan - Sariani Sariani; Saida Saida; Hidayat Arismunandar Katili; Annas Boceng (Savana Cendana, 2023)
Agricultural development aims to improve the living standards of farmers and the welfare of the community, one of which is fruit farming which has a strategic role in economic development at the local level to the national level. So, this study aims to identify the region's leading commodities and recommend land suitability as the basis for its development. This research uses quantitative-qualitative methods with a Location Quotient (LQ), Ship Share Analysis (SSA) approach, where this analysis is used to identify fruit commodities cultivated in an area to determine the base commodity, comparative and competitive advantages. Furthermore, a land analysis was carried out with the aim of determining the suitability of the superior commodity land in the South Tinangkung District. The results of the LQ-SSA analysis for the leading fruit commodities in South Tinangkung District are citrus plants. Furthermore, the analysis of land suitability for citrus crops, namely the criteria of sufficient compliance (S2) with an area of 3087.5 ha, and marginal (S3) covering an area of 1222.6 ha, with limiting factors in its development, namely texture, N, P, slopes and C-organic.